Formation of the tomato harvest depends on the application of bio-stimulators - Sievidov, V.; Alferov, O. (Scientific Progress & Innovations, 2025)
The cultivation of vegetable crops in protected soil is of critical importance for ensuring the population's supply of fresh produce. Special attention should be paid to tomato production, as this crop constitutes the largest share in the overall structure of vegetable production. This is particularly relevant for soil-based cultivation in greenhouse environments. The article presents the results of a study on the effects of different inoculation durations of tomato seeds in distilled water and with the application of biostimulants ABT and Epin-Extra on plant growth, development throughout the vegetative period, and overall yield performance. The research was conducted under field trial conditions within production-scale plastic greenhouses located at the State Biotechnological University, situated in the southeastern region of the Left-Bank Forest-Steppe zone of Ukraine. The study employed two indeterminate tomato hybrids, Matias F1 and Makhtos F1, both of which are well-adapted to the cultivation conditions prevalent in Ukraine. The duration of seed soaking or inoculation was varied and set at 4, 6, and 12 hours, respectively. Treatment of seeds with both distilled water and biostimulants accelerated plant development, as evidenced by the reduced duration of phenological growth stages. Specifically, inoculation with ABT reduced the duration of key developmental phases by 2–6 days (8–11 % compared to the control), while treatment with Epin-Extra led to a shift of 6–10 days (equivalent to 11–15 %). During the peak fruiting stage, significant differences in biometric parameters were observed depending on the treatment, with Epin-Extra – treated plants showing an increase of 7–12 % over the control. It was established that seed inoculation with Epin-Extra – a multifunctional growth regulator and adaptogen – proved effective in enhancing the yield of indeterminate tomato hybrids. In particular, a 12-hour inoculation period with this biostimulant resulted in the highest recorded yield of 17.5 kg/m², which exceeded the control by 24.3 %. These findings confirm the efficacy of biostimulants – particularly Epin-Extra – in enhancing seed biological activity, stimulating growth processes, and improving yield outcomes in tomato cultivation.